2022
DOI: 10.29333/iji.2022.1546a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Guided Inquiry Learning by Virtual Laboratory Assistance in Physics Learning in Indonesian Senior High Schools: A Meta-Analysis

Abstract: There are hundreds of studies on the effect of Guided Inquiry Learning by Virtual Laboratory Assistance (GILVLA) in Physics learning in Senior High School on students' learning outcomes in science. The studies have some contradictory results. In order to determine the impact of GILVLA on students' science learning outcomes and to gauge the degree of inter-study variation, a meta-analysis research was done. To find pertinent research that falls under the research's purview, the ERIC, Scopus, and Google Scholar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, the study only considered the learning material variable and has not yet considered the learning media or language variables. Another study that considered the learning material, learning media, display, ease of use, and language variables in the validity test analysis of VLBJS also found that VLBJS is valid to be used in experimental learning using VL [27,30,44,45]. Furthermore, subsequent research even shows that valid VLBJS can be an effective learning media in helping students understand practical learning concepts.…”
Section: B Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the study only considered the learning material variable and has not yet considered the learning media or language variables. Another study that considered the learning material, learning media, display, ease of use, and language variables in the validity test analysis of VLBJS also found that VLBJS is valid to be used in experimental learning using VL [27,30,44,45]. Furthermore, subsequent research even shows that valid VLBJS can be an effective learning media in helping students understand practical learning concepts.…”
Section: B Discussionmentioning
confidence: 95%
“…Several aspects need to be considered in creating a good VLBJS, such as (1) Relevance: The VLBJS is relevant to the learning objectives and materials that will be studied; (2) Interactive: The VLBJS is interactive and allows students to actively engage in learning; (3) User-friendly: The VLBJS is easy to use by students with an intuitive and easily understood interface; (4) Appropriate Language: The language used in the VLBJS should be following the student"s level of understanding and scientific writing standards; (5) Attractive: The VLBJS is attractive and can motivate students to learn; (6) Independent Learning: The VLBJS as a learning media supports the implementation of independent learning by students; (7) Effectiveness: The VLBJS is effective in improving students" understanding of the material being studied [25,29,30].…”
Section: B Virtual Laboratory-based Job Sheetmentioning
confidence: 99%
See 1 more Smart Citation
“…Inquiry learning is carried out using the procedures of scientific investigation [13] focusing on the skills to conduct research, interpret meaning, and attain new knowledge [13], [40]. Investigation activities promote students' independence to be actively and responsibly involved in the learning process [41] since these activities are students centered [20]. Additionally, inquiry learning supports students' collaboration [42], enabling them to establish knowledge and skills together in a group [10], [11].…”
Section: Discussionmentioning
confidence: 99%
“…The application of integrated learning in the assessment of digitized media increases creativity (Lashari et al, 2022;Sajidan et al, 2022). Virtual learning can guide student discovery in learning (Syahwin et al, 2022).…”
Section: The Development Of Digital E-books To Improve Students' …mentioning
confidence: 99%